ИНФОРМИРАНОСТ НА ПОПУЛАЦИЈАТА ЗА ГЛОБАЛНИОТ ПРОБЛЕМ СО КЛИМАТСКИТЕ ПРОМЕНИ - Александра Стамболиева; Михаил Кочубовски; Гордана Ристовска; Анета Костова (Institute of Public Health of the Republic of North Macedonia, 2019)
The EU Health Strategy „Together for Health“ acknowledged climate change as a health threat and stressed the role of the European Community to coordinate and respond rapidly to health threats globally and strengthen the capacities of countries (European Commission, 2008). The aim of the study was to determine the level of awareness of the population about the problem with the global climate change and the measures undertaken by the responsible bodies to handle the climate change. Material and methods: A pilot survey was conducted in December 2018 in the Republic of Macedonia by applying a questionnaire, which was an adapted version of the survey questionnaire (‚climate change‘ version 1), translated in Macedonian language and distributed on an interactive online platform. A total of 130 respondents answered the questionnaire. Results: The largest percentage (90.2%) of the respondents said air pollution was first thing they associated with the climate change, followed by the traffic density (41.7%) and waste management (41.7%). When it comes to responsibility, the National Government (33.8%) has the highest responsibility in comparison with international organizations (20%). Conclusion: The study has shown that there is certain level of awareness among the population concerning climate change and associated phenomena such as traffic density, fires and floods, but also strong campaigns has to be undertaken in order to raise public awareness.
Awareness of the population about the global problem with climate change
Keywords: climate change; public health; air pollution; information; awareness